Os métodos de extensão rural empregados pela Epagri no Alto Vale do Itajaí - SC - Lodi, Cesar Augusto (2013)
Rural Extension in Brazil has passed through many transformations in its way of acting and developing the work with farmers. The extension methods are extremely related to these transformations and, in a large extent, since the creation of the official services of Rural Extension, they arethe identity of the extensionist institutionsworker in the country.This study has analyzed the use of different methods of rural extension by the Empresa de Pesquisa de Agropecuária e Extensão Rural Santa Catarina (Epagri). The research was developed through the case study of the Unidade de GestãoTécnica 5, composed by 31 cities, located in the region called Alto Vale do Itajaí SC, with a cuali-quantative approach.The results point out that, in relation to the nature of the work done by extensionists, there is a predominance of office activities over field work, determined, mainly, by the demand of the paper work generated by governmental programs. The data demonstrated that about 50% of the farmers and 40% of the actions developed are associated to back activities, showing that a big part of the technician`s effort is associated to the demand of governmental programs. Considering the nature of the work methods, it was founda predominance of individual approach technics, they constitute 94.54% of the activities unfolded, existing among them a predominance of the office visiting. According to the technicians‟ point of view, the predominance of the individual approach is related to the nature of the work that they do and, the changes implemented in the Epagri managementdid not produced the expected effects in the increasing use of group methods.